Modulation of kinesin half-site ADP release and kinetic processivity by a spacer between the head groups. - Hackney, D.D.; Stock, M.F.; Moore, J.; Patterson, R.A. (Biochemistry, 2003)
A series of modifications of the junction of the neck linker and neck coil of dimeric Drosophila kinesin were constructed to determine the influence of head orientation and spacing on the ATPase kinetics. Ala(345) is the first residue in the coiled-coil of the neck, and its replacement with glycine or proline produces no significant change in the k(cat) or K(0.5(MT)) values for activation of their ATPase by microtubules (MTs) or in their k(bi(ratio)) value for the average number of ATP molecules hydrolyzed during a processive encounter with a MT. Addition or deletion of a single amino acid at the junction produces only modest changes with less than a 2-fold reduction in kinetic processivity. Insertion of a spacer of 6 or 12 additional amino acids at the neck linker junction increases the K(0.5(MT)) value by 3-4-fold with a corresponding decrease in kinetic processivity. The sliding velocities of all the mutant constructs under multimotor conditions are within 30% of the wild-type value. All the constructs with single residue changes exhibit half-site ADP release on binding to MTs. The constructs with long insertion, however, rapidly release both ADP molecules per dimer on binding to a MT, indicating that the steric constraints that prevent release of ADP from the tethered head of wild-type kinesin have been relieved by the long insertions. The constructs with long inserts have decreased kinetic processivity and dissociate from the MT during ATP hydrolysis 3-fold faster than wild-type.